Comparison of Albumin Level Test Results with Serum and EDTA Plasma Samples : Comparison of Albumin Level Test Results with Serum and EDTA Plasma Samples - Rinza Rahmawati Samsudin; lihabi lihabi; Fitrotin Azizah; Haris Rizki Maulana (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
Blood albumin level testing is an important parameter in assessing nutritional status and liver function. In clinical laboratory practice, the use of serum or EDTA plasma as biological samples remains a subject of debate, particularly regarding the efficiency and accuracy of results. This study aims to compare albumin level test results using serum and EDTA plasma samples. Blood samples were collected from 20 participants and analyzed using spectrophotometry. The average albumin level in serum samples was 4.285 g/dL, while in EDTA plasma it was 4.280 g/dL. The Shapiro-Wilk normality test indicated a normal data distribution (p>0.05), and the paired t-test yielded a p-value of 0.804 (>0.05), indicating no significant difference between the two sample types. These findings suggest that EDTA plasma can serve as an alternative to serum in albumin testing, with the advantage of improved processing efficiency.